2011
DOI: 10.1242/dev.059568
|View full text |Cite
|
Sign up to set email alerts
|

VAB-10 spectraplakin acts in cell and nuclear migration in Caenorhabditis elegans

Abstract: SUMMARYCytoskeletal regulation is important in cell migration. The Caenorhabditis elegans gonadal distal tip cells (DTCs) offer a simple model with which to investigate the mechanism of cell migration in organogenesis. Here, we report that one of the spectraplakin isoforms, VAB-10B1, plays an essential role in cell and nuclear migration of DTCs by regulating the actin and microtubule (MT) cytoskeleton. In the vab-10(tk27) mutant, which lacks VAB-10B1, alignment of filamentous (F)-actin and MTs was weakly and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…This type of cross-talk often requires mechanical coupling between the two cytoskeletal networks by proteins or protein complexes that act as physical cross-bridges (Salmon et al ., 2002; Rothenberg et al ., 2003; Wittmann et al ., 2003; Miller et al ., 2004; Rosales-Nieves et al ., 2006; Lee and Suter, 2008; Applewhite et al ., 2010). The spectraplakins are one such family of giant cytoskeletal cross-linking proteins that have been highly conserved across most animal lineages (Lee et al ., 2000; Röper et al ., 2002; Röper and Brown, 2003; Jefferson et al ., 2004; Sonnenberg and Liem, 2007; Kim et al ., 2011; Suozzi et al ., 2012). Wherever studied genetically, spectraplakins are found to be essential genes that play multiple roles in development.…”
Section: Introductionmentioning
confidence: 99%
“…This type of cross-talk often requires mechanical coupling between the two cytoskeletal networks by proteins or protein complexes that act as physical cross-bridges (Salmon et al ., 2002; Rothenberg et al ., 2003; Wittmann et al ., 2003; Miller et al ., 2004; Rosales-Nieves et al ., 2006; Lee and Suter, 2008; Applewhite et al ., 2010). The spectraplakins are one such family of giant cytoskeletal cross-linking proteins that have been highly conserved across most animal lineages (Lee et al ., 2000; Röper et al ., 2002; Röper and Brown, 2003; Jefferson et al ., 2004; Sonnenberg and Liem, 2007; Kim et al ., 2011; Suozzi et al ., 2012). Wherever studied genetically, spectraplakins are found to be essential genes that play multiple roles in development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that when DTCs migrate dorsally on the hypodermal BM, the DTC forms a single lamellipodium in the direction of migration and then retracts its trailing edge as it shifts its migration to the dorsal BM (Kim et al, 2011). This mode of migration may depend on the contractile activity of NMY-2 and could be necessary for the DTC to transition from the hypodermal BM to the dorsal BM.…”
Section: Discussionmentioning
confidence: 99%
“…Each DTC forms a close-fitting cap over the 6–10 germ cells and had been thought to maintain this morphology during the course of its migration 2 . Unexpectedly, however, DTCs were found to change their shape dramatically at the first turn 3 . DTCs that expressed GFP-moesin, which labels cortical actin filaments, were analyzed by confocal microscopy and shown to extend a single large lamellipodium dorsally when they make the first turn (Fig.…”
Section: Dtcs Change Their Morphology During Dorsal Migrationmentioning
confidence: 98%
“…The DTCs extend lamellipodia at the onset of this turn and thus place their nuclei near the leading edge. This nuclear translocation requires the action of VAB-10B1, one of the spectraplakin isoforms in C. elegans 3 . Spectraplakins are large cytoplasmic proteins that regulate the cytoskeleton 4 - 6 .…”
Section: Vab-10b1/spectraplakin Acts In Nuclear Positioningmentioning
confidence: 99%
See 1 more Smart Citation